A natural strategy to improve the shelf life of the loaf bread against toxigenic fungi: The employment of fermented whey powder. (9th October 2019) - Luz, Carlos; Rodriguez, Lorena; Romano, Raffaele; Mañes, Jorge; Meca, Giuseppe
Abstract : Whey powders are used as food ingredients in many applications, from bakery goods, soups and sauces to baby food. The objective of the study was to evaluate the antifungal property of a whey‐based medium (WM) fermented by lactic acid bacteria. The antifungal activity of the WM was evaluated using antifungal tests on solid and liquid media. MIC and MFC ranged from 15.6 to 250 mg/mL and 62.5 to 250 mg/mL, respectively. Using fermented WM for dough preparation produced a reduction of Penicillium expansum growth of 0.5–0.6 log CFU/g and an improvement in shelf life of 1–2 days in relation to control bread.